Testing the birth attitude profile scale in a Swedish sample of women with fear of birth - Ingegerd Hildingsson; Christine Rubertsson (Taylor & Francis Group, 2021)
Objective The aim of this study was to explore the "Birth Attitude Profile Scale (BAPS)" in a selected sample of women with fear of birth. Another aim was to develop profiles of women according to their birth attitudes and levels of childbirth fear in relation to background characteristics. Methods A secondary analysis of data collected in two different samples of women with fear of birth. Data were collected by a questionnaire in gestational week 36 and background data from mid-pregnancy. A principal component analysis and a cluster analysis were performed of the combined sample of 195 women. Results The principal component analysis revealed four domains of the BAPS: "personal impact, birth as a natural event, freedom of choice and safety concerns". When adding the fear of birth scale, two clusters were identified: one with strong attitudes and lower fear, labeled "self-determiners"; and one with no strong attitudes but high levels of fear, labeled "fearful." Women in the "Fearful" cluster more often reported previous and current mental health problems, which were the main difference between the clusters. Conclusion The BAPS instrument seems to be useful in identifying birth attitudes in women with fear of birth and could be a basis for discussions and birth planning during pregnancy. Mental health problems were the main difference in cluster membership; therefore, it is important to ask women with fear of childbirth about physical, mental and social aspects of health. In addition, a qualitative approach using techniques such as focus groups or interviews is needed to explore how women come to form their attitudes and beliefs about birth.